Australian ethnography and frontier history: do we know what we think we know? - Lever, Michael (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The early European settlement of much of Australia was typified by the advance of squatters well beyond boundaries permitted by governments of the time (Reynolds 2021). This article explores existing understandings of the relationship between such a settler, Peter Beveridge, and local Aboriginal people through a critical reading of documentary resources many of which were written by Beveridge himself. This article concludes that little of Peter Beveridge’s claims regarding Aboriginal people or his knowledge about their lifestyles should be accepted without careful scrutiny.